EP323 Extended nerve-sparing radical hysterectomy. (1st November 2019) - Kato, T; Tsukada, T; Yoneoka, Y; Kato, M; Tanase, Y; Uno, M; Ishikawa, M
Abstract : Introduction/Background: Based on our cadaveric studies on the running of autonomic nerves in the female pelvis we modified the Japanese traditional nerve-sparing radical hysterectomy (NSRH) to raise radicality of the cardinal ligament. Since cervical cancer FIGO stage IIB was also applied to the extended NSRH, the oncologic outcome was examined. Methodology: The extended NSRH was performed using the ureterohypogastric fascia that surrounded the autonomic nerves as an indicator of dissection. The ureterohypogastric fascia were identified during the dissection of the ureter. The study included 108 patients with cervical cancer who underwent the extended NSRH between 2006 and 2017. Their FIGO stages (2008) were 65 IB1, 17IB2, 6IIA1, 1IIA2, and 19IIB. According to pTNM classification, they were divided into 4 groups such as pT1b, 2aN0, pT1b, 2aN1, pT2bN0, and pT2bN1. None of the pT1b, 2aN0 group received adjuvant therapy (radiotherapy, RT; 2006–2010, Intensity modulated RT, IMRT; 2011–2014, and Concurrent chemotherapy with IMRT, CC/IMRT; 2015–2017). Results: Their pTNM classification was 65 pT1b, 2aN0, 11 pT1b, 2aN1, 9 pT2bN0, and 23 pT2bN1. The median of number of positive pelvic nodes were three. The para-aortic lymph node metastasis was observed in 22% (5/23) of patients with pT2bN1. After the median follow-up of 74 months (range 8–145), 25% (27/108) had progressed disease, and 13% (14/108) patients died. The 5-year 1ocal recurrence free survival was 89% in the pT1b, 2aN0 group, 75% in the pT1b, 2aN1, 100% in the pT2bN0, and 77% in the pT2bN1. The 5-year overall survival was 96%, 72%, 100%, and 65%, respectively. Two 2 months after the surgery none needed to perform self-catheterization. Conclusion: By the procedures of our extended NSRH, patients with negative nodes survived for long time with no evidence of disease. The 5-year OS of node-positive was around 70%, and this improvement could be expected from the effect of adjuvant CC/IMRT. Disclosure: Nothing to disclose.